CORRESPONDENCE ANALYSIS PADA HUBUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KOPI PAGARALAM - Irmeilyana, Irmeilyana; Ngudiantoro, Ngudiantoro; Rodiah, Desty (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
Pagaralam is one of the coffee-producing districts in South Sumatra (Sum-Sel). Pagaralam coffee farming is a hereditary business, where the majority of land processing is still traditional. This is related to working capital and farmers' income. This study aims to analyze the factors that affect the income of Pagaralam coffee farmers by using correspondence analysis. There are 30 variables or factors studied. Each variable is divided into several categories. The categories of each variable are described graphically with the categories of income variable. Primary data were obtained from 196 respondents who were selected based on purposive sampling technique. There are 13 factors that affect the income of respondents, namely: number of dependents, number of trees, age of the trees, number of female workers from outside the family, frequency of fertilization, frequency of herbicide application, production of harvest, production outside of harvest, gross income, minimum price of coffee beans, the maximum price of coffee beans, economic status and land productivity. There are 8 of the 13 factors that predominantly characterize the profile of net income level of Pagaralam coffee farmers. In general, the factor that must be considered in coffee farming is land productivity which is also related to production costs in land processing and crop production, as well as external factors regarding the market price of coffee.